Customer value, shareholder wealth, community wellbeing : a roadmap for companies and investors - Kilroy, Denis; Schneider, Marvin (Palgrave Macmillan, 2017)
This book provides a roadmap for leaders of listed companies to follow in order to build enduring institutions that create value for customers and wealth for shareholders on an ongoing basis, in ways that also enhance the wellbeing of all other legitimate stakeholders - including the wider community and the environment. Customer Value, Shareholder Wealth, Community Wellbeing is an inspirational work that confirms the very positive role that a more expansive, more inclusive and more conscious approach to business, can play within our society. It incorporates a breakthrough in understanding in applied corporate finance and business economics centred on the Bow Wave of Expected Economic Profits. This construct provides an economic underpinning for a new and more socially responsible business paradigm - demonstrating for the first time exactly how the performance produced by management in the market for their company's products and services, translates into the capital market outcomes experienced by shareholders.
Keywords: Social responsibility of business.; Industrial management.; elektronické knihy; electronic books